Development of magnetic structures by micro-magnetofluidic techniques - Varma, Vijaykumar Babulalji (2017)
Microfluidics is a branch of fluid dynamics which deals with investigations of fluid behavior at the micron scale, characterized by low Reynolds number, which results in laminar flow. The field of microfluidics is of high significance due to its broad spectrum of applications, including as a Lab-on-a-Chip (LoC) platform. For example, droplet microfluidics offers a large increase in the multiplex capability desired for most LoC; applications the droplets act as individual pl to nl volume range containers. Integration of magnetofluidics with microfluidics can provide control of droplets in the flow to develop a practical LoC device. The resulting domain of droplet micro-magnetofluidics (MMF) offers the excellent capability for the wireless and remote control of droplets, leading to versatile droplet micro-magnetofluidics (DMMF) applications. Magnetic fluids in the ferrohydrodynamic regime (termed as ferrofluids), exhibit liquid magnet like behavior. Ferrofluids exhibit a significant response to both uniform and hybrid magnetic fields. Hence, the behavior of ferrofluid droplets (FD) and magnetic Janus droplets (MJD) exposed to uniform and hybrid magnetic fields have been investigated in a microfluidic environment. A MMF setup by integrating microfluidics and magnetofluidics have been developed. Various designs of microfluidic chips were employed for LoC droplet generation at different length scales for DMMF investigations. A droplet MMF numerical model was developed to elucidate the dynamic behavior of ferrofluid droplets in uniform as well as hybrid magnetic fields. This model simulated droplet generation, droplet deformation, and merging of droplets in uniform magnetic fields. Experimental and numerical investigations for continuous flow MMF and investigations of MMF spreading of a ferrofluid core stream clad by diamagnetic streams have been performed. A water-based ferrofluid was utilized as the magnetic phase and aqueous glycerol as the diamagnetic phase. The effect of applied uniform magnetic field was investigated for a range of flow rates, flow rate ratio, viscosity, magnetic particle concentration and ferrofluid susceptibility. The role of diffusion of particles, drift velocity of magnetic particles, and convective diffusion was studied. We found that difference in magnetic susceptibility between the core and diamagnetic streams led to a distortion of the magnetic field, resulting in a magnetic force acting on the ferrofluid. Spreading was observed mainly near the channel walls due to the lower flow velocity near the walls. Convective diffusion is the main factor for MMF spreading, which was favored at low flow rates, low flow rate ratio and high magnetic field. After investigating continuous flow behavior, the studies were extended to DMMF and demonstrated LoC droplet merging and fabrication of magnetic Janus particles. The combination of FD and uniform magnetic field offers wireless, programmable remote control, which is useful for LoC applications. LoC experiments and numerical studies were performed to investigate FD behavior in uniform magnetic fields. The dynamic behavior of FD was evaluated by investigating droplet size, aspect ratio, droplet velocity and droplet spacing. The size, shape, velocity and inter-droplet spacing of these droplets could be controlled by tuning magnetic field strength, ferrofluid susceptibility, viscosity and flow rates. The droplet micro-magnetofluidic numerical model found to be in good agreement with experimental results. Controlled LoC merging of droplets is a challenge. This challenge was addressed by numerical modeling and experimental studies of uniform magnetic field induced merging of ferrofluid based droplets; control of droplet velocity and merging was achieved. Merging and mixing of composite droplets, such as color dye+ magnetite, was demonstrated. Our numerical results were found to be in good agreement with experiments. These studies are useful for wireless and programmable droplet merging as well as mixing relevant to biosensing, bioassays, microfluidic-based synthesis, reaction kinetics, and magnetochemistry. These experimental and simulation findings were utilized to develop a DMMF platform for magnetic Janus particle (MJP) fabrication. This system is capable of magnetically controlled, selective LoC polymerization, resulting in the synthesis of MJP. Since the method is wash-less and does not use oils or surfactants, MJP are “ready to use”. The effect of flow rate and magnetic field on the particle size, magnetization, and polymeric properties of the MJP was investigated. Particle synthesis at high flow rates of 4 ml/h was demonstrated. The properties of synthesized MJP were assessed and the application of the particles for protein detection was demonstrated. The development of MMF and droplet MMF techniques relevant to LoC applications have been demonstrated. These studies are useful for the development of next-generation technology with multiplexing, wireless, programmable, and remote control capabilities. The DMMF investigations demonstrate control of magnetic droplets on a LoC platform using uniform magnetic fields, which overcomes the limitations of nonuniform magnetic field based systems. DMMF was utilized to develop magnetically controlled LoC Janus particle synthesis. Such particles are useful for bioassays, tagging of particles or cells and protein detection.